Relationship between weight-adjusted waist circumference index and prevalence of gallstones in U.S. adults: a study based on the NHANES 2017-2020 - Ke, Bin; Sun, Ying; Dai, Xin; Gui, Yang; Chen, Song (Frontiers in Endocrinology, 2023)
Objective: We aimed to assess the association between weight-adjusted waist circumference index (WWI) and gallstone prevalence in US adults.: We selected individuals from the National Health and Nutrition Examination Survey (NHANES) database from 2017 to 2020 and used logistic regression analyses, subgroup analyses, and dose-response curves to assess the association between WWI and gallbladder stone prevalence and age, sex, and ethnicity. Results: A total of 7971 participants aged ≥20 years were enrolled in our study; 828 Database 删除[棒槌]:patients had a self-reported history of gallstones. After correcting for confounders, for each unit of WWI after Ln conversion, the prevalence of gallbladder stones increased by 34% (OR=1.34, 95% CI:1.20, 1.50). Dose-response curves showed a positive correlation between WWI and gallbladder stone prevalence.According to the subgroup analysis, the positive association between TyG index and high-frequency HI was more significant in males(OR=1.34, 95% CI:1.07, 1.69), <40 years old(OR=1.42, 95% CI:1.18, 1.71), white people Americans(OR=1.35, 95% CI:1.08, 1.68) and other races(OR= 1.56, 95% CI:1.13, 2.14).Higher WWI was positively associated with the prevalence of gallbladder stones and was associated with gender, age, and ethnicity. This is noteworthy, although a causal relationship could not be established.